2018
DOI: 10.7717/peerj.5542
|View full text |Cite
|
Sign up to set email alerts
|

Balanced and positively worded personality short-forms: Mini-IPIP validity and cross-cultural invariance

Abstract: BackgroundThe Mini-IPIP scales (Donellan et al., 2006) are possibly one of the most commonly used short inventories for measuring the Big Five Factors of personality. In this study, we aimed to investigate the psychometric properties of two Mini-IPIP Spanish short forms, one balanced and one positively wording (PW).MethodTwo samples, one from native Spanish speakers and another from native English speakers, made up a total of 940 participants in this study. The short forms were translated and adapted based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
0
15
1
2
Order By: Relevance
“…The study of the positive and negative affect by means of ESEM models is relatively new [29,30], and there is a lack research analyzing the PANAS structure with this approach, that allow analyzing the structure of positive and negative affect without the restrictions of the CFA models. The results, also revealed a ESEM three factor model as adequate, similar to previous research suggesting the adequacy of a three factor model [15,21,24], although in the present study, the dimensions found for the NA factor were composed of different items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the positive and negative affect by means of ESEM models is relatively new [29,30], and there is a lack research analyzing the PANAS structure with this approach, that allow analyzing the structure of positive and negative affect without the restrictions of the CFA models. The results, also revealed a ESEM three factor model as adequate, similar to previous research suggesting the adequacy of a three factor model [15,21,24], although in the present study, the dimensions found for the NA factor were composed of different items.…”
Section: Discussionmentioning
confidence: 99%
“…This, may better represent the latent construct of affect in terms of a psychological point of view. With this regard, recent studies have analyzed the structure of positive and negative affect by means of the ESEM approach [29,30]. Therefore, and as proposed by Ortuño-Sierra et al [31], studies analyzing the factor structure of the PANAS are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…El modelo principal (MP) establecido por Donnellan et al (2006) no ha presentado adecuados índices de ajuste, lo que coincide con algunos estudios (Leong et al, 2019;Oliveira, 2019;Perry et al, 2020) y difiere de otros (Cooper et al, 2010;Czerwiński & Atroszko, 2020;Li et al, 2012;Simkin et al, 2020). Por otro lado, dentro del estado del arte se hallaron dos modelos (M1 y M2) que correlacionaban errores para obtener un buen ajuste del Mini-IPIP (Martínez-Molina & Arias, 2018;Perry et al, 2020); al calcular estos dos modelos se halló que los errores correlacionados mejoraban la bondad de ajuste, pero afectaban la fiabilidad. En especial el modelo M2, el cual mantenía mayor número de errores correlacionados, mostró disminución en el coeficiente de confiabilidad de apertura.…”
Section: Discussionunclassified
“…The version used in the present study is the positively worded version, which differs from the original Mini-IPIP in that all the items are positively worded. The Spanish Mini-IPIP-PW has shown high levels of reliability and convergent and predictive validity [ 52 ]. The Cronbach’s alpha and the Omega coefficients for the Spanish Mini-IPIP-PW in the present study were all adequate, with the exception of factors E and N (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%